AI Scholars Program: Scaling AI Literacy Through K-12 Outreach - Tian, Xiaoyi; Rajapaksha, Yasitha; Limke, Ally; DiMarco, Clara; Dobar, Emily Bryans; Hill, Marnie; Payton, Jamie; Barnes, Tiffany (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
As artificial intelligence (AI) becomes increasinglyintegrated into daily life, there is a critical need fordeveloping AI literacy across all educational levels.However, current AI education remains largely confined tocollege-level computer science classrooms with limitedaccess for K-12 learners. We present the AI ScholarsProgram, a novel approach that addresses the AI educationgap by preparing college computing students to serve as AIeducation ambassadors in their communities and empoweringK-12 teachers to adopt AI education practices in theirclassrooms. This experience report presents the curriculumand its outcomes after one round of refinement. The programoffers structured AI learning through bi-weekly webinars,resources, and collaborative opportunities to form teamsand conduct community outreach projects. Our programinvited 63 scholars from 30 institutions across the U.S.,including 51 college students and 12 K-12 teachers. Theiroutreach impacted over 230 K-12 learners. We examineprogram outcomes for participants and projects throughpre/post surveys measuring computing attitudes andself-efficacy for teaching AI, scholar interviews, andoutreach project reports. We share lessons learned andchallenges for designing similar programs, highlighting theimportance of involving educators for effectivecommunity-engaged AI education. The program creates asustainable pipeline for college students to developtechnical skills and leadership while addressing K-12 AIeducation shortages. We contribute insights for scaling AIliteracy and broadening participation in computing.